Analysis of Educational Spaces Design Methods for Educable Mentally Disable Children: A Case study on 6-17 years old childrens (EMARA: Indonesian Journal of Architecture, 2018)
This study aims to investigate and analyse design and optimisation methods of educational and recreational environments for educable mentally disabled children. This study is conducted using a descriptive-analytical method based on library research, documents and field surveys. The research studied sixty mentally disabled children aged 6-17 years, twenty instructors and sixty mothers through purposive sampling. Then the quantitative data of questionnaires and the qualitative data of interviews and paintings are analysed using SPSS and Excel. The results of this research determine the useful criteria used to design an attractive and friendly environment for mentally disabled children. In addition to promoting the sense of safety and security in these spaces, it improves recreational activities of mentally disabled children both individually and collectively.